Broad support for regulating the clinical implementation of future reproductive techniques. Issue 1 (28th November 2017) - Hendriks, S; Vliegenthart, R; Repping, S; Dancet, E A F
Abstract: STUDY QUESTION: Do gynaecologists, infertile patients and the general public, consider that regulation of the clinical implementation of stem cell-based fertility treatments is required? SUMMARY ANSWER: There is broad support from gynaecologists, patients and the general public for regulating the clinical implementation of future stem cell-based fertility treatments. WHAT IS KNOWN ALREADY: There is debate on the need to regulate the clinical implementation of novel techniques. Regulation may hinder their swift adoption and delay benefits for patients, but may prevent the implementation of ineffective or harmful techniques. Stem cell-based fertility treatments, which involve creating oocytes or spermatozoa by manipulating stem cells, are likely to be implemented in clinical practice in the near future and will probably impact future generations as well as the current one. STUDY DESIGN, SIZE, DURATION: A cross-sectional survey was conducted among gynaecologists working in fertility clinics ( n = 179), patients with severe infertility ( n = 348) and a representative sample of the general public ( n = 1250). The questionnaire was disseminated in the Netherlands in the winter of 2015–2016. PARTICIPANTS/MATERIALS, SETTING, METHODS: The newly developed questionnaire was reviewed by experts and tested among the general public. The questionnaire assessed whether participants wanted each of nine potential negative consequences of the clinical implementation of stem cell-based fertility treatments to be regulated. In addition, the importance of all negative and positive potential consequences, the appropriate regulatory body and its need to consult with advisors from various backgrounds was questioned. MAIN RESULTS AND THE ROLE OF CHANCE: In total, 958 respondents completed the questionnaire (response rate: 54%). A large majority of each participant group (>85%) wanted regulation, for at least one potential negative consequence of the clinical implementation of stem cell-based fertility treatments. The majority of all participant groups wanted regulation for serious health risks for intended parents, serious health risks for children and the disposal of human embryos. Regulation for out-of-pocket costs and the burden of treatment received little support. The majority of gynaecologists and the general public, but not the patients, requested regulation for the risk of minor congenital abnormalities, the success rates and the naturalness of treatments. Nevertheless, the majority of patients did consider the former two potential negative consequences important. The majority of all groups preferred a national bioethics committee as the regulatory body. This committee should consult with advisors from various backgrounds and should consider the broader context of potential consequences of the stem cell-based fertility treatments. LIMITATIONS, REASONS FOR CAUTION: This empirical study focuses on only three stakeholder groups. This study reports on the perspective of the majority and this is not per definition the morally right perspective. The transferability of our findings to other cultures and other techniques remains unclear. WIDER IMPLICATIONS OF THE FINDINGS: A national bioethics committee, consulting with advisors from various backgrounds, should regulate the clinical implementation of future stem cell-based fertility treatments. Whether this broad support for regulation applies to novel techniques from other fields of medicine should be examined. STUDY FUNDING/COMPETING INTEREST(S): The Young Academy of the Royal Netherlands Academy of Arts and Sciences. None of the authors has any conflict of interest to declare. TRIAL REGISTRATION NUMBER: Not applicable.